Work Versus Leisure Screen Time and Mental Wellness in Working-Age Adults - Kofi Nyantakyi Appiah; Divyanshu Kumar Singh; Nathanael Adu; Edward Edem Nartey (Jurnal Psikologi Teori dan Terapan, 2026)
Background: Contextual variations in screen time between work and leisure use remain understudied, with few analyses decomposing these differential associations with mental wellness or testing their robustness. Objective: This preregistered cross-sectional study (OSF.IO/Q6HYZ) examined the association between work and leisure screen time and mental wellness using the Screentime vs. Mental Wellness Survey 2025 dataset. Method: Multiple linear regression with occupation fixed effects, quantile regression, and moderation analyses were employed. Robustness was assessed using MM estimation, occupation-clustered standard errors, winsorization, and specification curve analysis (156 models). Results: Work screen time showed a stronger negative association with mental wellness than leisure screen time (full model: βwork = −3.89, SE = 0.79, p < 0.001 vs. β_leisure = −2.41, SE = 0.69, p < 0.001; R2 = 0.938; Cohen's d = 0.84 vs. 0.36). Quantile regression revealed amplified associations among heavy users (Q4: β_work = −17.98, SE = 3.20, p < 0.001). Remote workers exhibited 41% attenuation (β = 2.73, p = 0.051), and students showed 22% resilience (β = 1.36, p = 0.037). Software developers (β = −5.80) and teachers (β = −4.90) had the strongest associations. Conclusion: Work screen time is strongly associated with lower mental wellness than leisure screen time across all specifications, supporting occupation-specific digital-wellness strategies. Abstrak Latar Belakang: Variasi kontekstual dalam waktu layar, khususnya antara penggunaan untuk bekerja dan bersantai, masih kurang diteliti, dengan sedikit analisis yang menguraikan asosiasi diferensial ini terhadap kesejahteraan mental atau menguji ketahanannya. Tujuan: Studi potong lintang praregistrasi ini menguji asosiasi antara waktu layar kerja dan waktu layar rekreasi dengan kesejahteraan mental menggunakan dataset Screentime vs Mental Wellness Survey 2025 (N=400). Metode: Regresi linier berganda dengan efek tetap okupasi (R² = 0.407–0.938), regresi kuantil (fokus Q4), moderasi oleh status kerja jarak jauh dan mahasiswa, serta uji ketahanan termasuk estimasi-MM, standard error klaster, winsorisasi, dan kurva spesifikasi (156 model, 92% signifikan). Hasil: Waktu layar kerja menunjukkan asosiasi negatif yang lebih kuat dengan kesejahteraan mental dibandingkan dengan waktu layar rekreasi (β = −3.89 vs. β = −2.41; p < 0.001; 65% lebih besar). Regresi kuantil memperkuat efek pada pengguna berat (Q4: β = −17,98; p < 0,001). Pekerja jarak jauh menunjukkan perlindungan 41% (β = 2.73; p = 0,051), dan mahasiswa menunjukkan ketahanan 22% (β = 1.36; p = 0,037). Keimpulan: Waktu layar kerja secara konsisten memiliki asosiasi negatif yang lebih kuat dengan kesejahteraan mental daripada penggunaan rekreasi, mendukung strategi kesejahteraan digital yang ditargetkan berdasarkan jenis pekerjaan.